LEBAK DISTRICT’S STRATEGY FOR PROMOTING BADUY TOURISM DURING THE PANDEMIC - Ukke Inggryd Aulia; Leila Mona Ganiem (Journal of Innovation Research and Knowledge, 2024)
The Covid-19 pandemic has significantly impacted various sectors, including tourism, which is a vital sector for generating foreign exchange and contributing to economic development. Tourism plays a crucial role in creating and expanding business opportunities, increasing community and government income, and fostering environmental and cultural preservation. This study applies John December's Computer-Mediated Communication (CMC) Theory, focusing on the marketing communication mix. The aim is to evaluate the promotional strategies employed by the Culture and Tourism Office of Lebak Regency for tourist destinations and the creative economy during the pandemic. This qualitative research utilizes data obtained through observation, interviews, literature reviews, and documentation. The findings indicate that the Culture and Tourism Office of Lebak Regency has not fully optimized the use of digital media in promoting Baduy cultural tourism and its creative economic impacts